2004
DOI: 10.1158/1078-0432.ccr-04-1212
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Tumor Cell Radiosensitivity and Abrogation of G2 and S Phase Arrest by the Hsp90 Inhibitor 17-(Dimethylaminoethylamino)-17-demethoxygeldanamycin

Abstract: Purpose: Because of the potential for affecting multiple signaling pathways, inhibition of Hsp90 may provide a strategy for enhancing tumor cell radiosensitivity. Therefore, we have investigated the effects of the orally bioavailable Hsp90 inhibitor 17-(dimethylaminoethylamino)-17-demethoxygeldanamycin (17-DMAG) on the radiosensitivity of human tumor cells in vitro and grown as tumor xenografts.Experimental Design: The effect of 17-DMAG on the levels of three proteins (Raf-1, ErbB2, and Akt) previously implica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
91
1
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 93 publications
(101 citation statements)
references
References 21 publications
7
91
1
2
Order By: Relevance
“…A number of different treatment protocols using Hsp90 inhibitors, including 17DMAG, have been reported to enhance the radiosensitivity of human tumor cell lines (8)(9)(10)(11)(12). The radioresponse of three cell lines (DU145 prostate carcinoma, PSN1 pancreatic carcinoma, and MiaPaCa pancreatic carcinoma) exposed to 50 nmol/L 17DMAG for 16 hours prior to irradiation are shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A number of different treatment protocols using Hsp90 inhibitors, including 17DMAG, have been reported to enhance the radiosensitivity of human tumor cell lines (8)(9)(10)(11)(12). The radioresponse of three cell lines (DU145 prostate carcinoma, PSN1 pancreatic carcinoma, and MiaPaCa pancreatic carcinoma) exposed to 50 nmol/L 17DMAG for 16 hours prior to irradiation are shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…17DMAG, in contrast to 17AAG, is water-soluble, orally bioavailable, and does not seem to undergo extensive metabolism to toxic species (20,21). In these studies, 17DMAG was found to enhance the in vitro radiosensitivity of three human cell lines originating from three different tumor histologies and to result in a greater than additive increase in radiation-induced tumor growth delay in a human tumor xenograft model (8). Whereas a number of radioresponse-associated proteins decreased after 17DMAG exposure, the radiosensitization appeared to correlate best with a decrease in the levels of ErbB2 (8).…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…Furthermore, several agents inactivating Chk1 are reported to abrogate G 2 arrest and simultaneously sensitize tumor cells to DNAdamaging agents (Kohn et al, 2003;Kawabe, 2004). Recently, Chk1 has been identified as an Hsp90 client and 17-AAG-mediated depletion of Chk1 has been shown to sensitize tumor cells to replication stress induced by nucleoside analog gemcitabine (Arlander et al, 2003;Bull et al, 2004).…”
Section: Introductionmentioning
confidence: 99%